When do people prefer dominant over prestigious political leaders?. (1st March 2021) - Jiménez, Ángel V.; Flitton, Adam; Mesoudi, Alex
Abstract: Abstract: Previous research has sought to explain the rise of right-wing populist leaders in terms of the evolutionary framework of dominance and prestige. In this framework, dominance is defined as high social rank acquired via coercion and fear, and prestige is defined as high social rank acquired via competence and admiration. Previous studies have shown that right-wing populist leaders are rated as more dominant than non-populist leaders, and right-wing populist/dominant leaders are favoured in times of economic uncertainty and intergroup conflict. In this paper, we explore and critique this application of dominance–prestige to politics. First, we argue that the dominance–prestige framework, originally developed to explain inter-personal relationships within small-scale societies characterised by face-to-face interaction, does not straightforwardly extend to large-scale democratic societies which have frequent anonymous interaction and complex ingroup–outgroup dynamics. Second, we show that economic uncertainty and intergroup conflict predict a preference not only for dominant leaders, but also for prestigious leaders. Third, we show that perceptions of leaders as dominant or prestigious are not fixed, and depend on the political ideology of the perceiver: people view leaders who share their ideology as prestigious, and those who oppose their ideology as dominant, whether that ideology is liberal or conservative. Fourth, we show that political ideology is a stronger predictor than economic uncertainty of preference for Donald Trump vs Hillary Clinton in the 2016 US Presidential Election, contradicting previous findings that link Trump's success to economic uncertainty. We conclude by suggesting that, if economic uncertainty does not directly affect preferences for right-wing populist leaders, other features of their discourse such as higher emotionality might explain their success.